Biossorção de metais (Cd, Pb e Cr) em águas utilizando torta de sementes de Crambe abyssinica Hochst - Rubio, Fernanda (2012)
Due to the intense pollution of the waters, is necessary the search for options which provide the remediation of the contaminated hydric resources, therefore the objective of this work was to evaluate the cake of crambe seeds (Crambe abyssinica Hochst) as a biosorbent in the removal of toxic heavy metals cadmium (Cd), lead (Pb) and chromium (Cr) in waters. The biomass was characterized by scanning electron microscopy (SEM), infrared spectroscopy (IR) and determination of the point of zero charge (pHpzc). The results demonstrate a favorable structure for the adsorption both by irregular morphology presented by SEM and by the functional groups indicated by IR. The result assigned by the pHpzc test of 5.5, the adsorption of cations the pH of the solution must be higher than the pHpzc. For the verification of the optimal conditions for the adsorption tests, the following factors were evaluated: variation effect of the biosorbent mass (200 to 1200 mg), pH of the solution (5.0, 6.0 and 7.0) and contact time (20 to 180 min). The results indicate that the best mass for the studies of the 3 metals (Cd, Pb and Cr) was of 400 mg. For the pH test, the solutions with pH 6.0 provided the best adsorption of Cd and Cr, while for the Pb the best pH was 7.0. In the kinetic study, the equilibrium was achieved in approximately 60 min for the Cd, 20 min for the Pb and 80 min for the Cr. After determinated the ideal conditions, tests were performed for the construction of the isotherms, ranging the concentration of the metals from 10 to 90 mg L-1. The bests adjusts for Cd, Pb and Cr followed the models of Freundlich and Dubinin-Radushkevich (D-R), describing a multilayer adsorption and with chemical nature, still confirmed by the pseudo second-order test. The estimated value of the maximum capacity of adsorption by biosorbent mass (qm) for Cd was 19.342 mg g-1, for Cr 6.807 mg g-1 and for Pb was not possible to determinate this parameter due to the non-linearity presented. The influence of the temperature was studied for the determination of the thermodynamic parameters, which was performed using optimal conditions ranging temperature from 25 to 65 ºC. The positive values of ΔH e ΔS indicate a endothermic process and a randomness system, respectively. Only for the Pb was found negative ΔG, referring to a spontaneous adsorption. The percentage of removal of the ions was of: Pb 97%, Cd 76% e Cr 45%. In the desorption, only the Cd was able to be successfully recovered. Using the same conditions applied for the biosorbent crambe, comparative tests of adsorption and desorption were performed using commercial activated coal. By the obtained results and knowing that the cake of crambe seeds are a byproduct available in high scale and which did not undergone any previous treatment, was verified high applicability of this material as biosorbent in the treatment of contaminated waters with Cd, Pb and Cr, presenting itself as a viable alternative for the decrease of the environmental impacts, because it s a byproduct and it present itself as a natural and sustainable material